Sistem Manajemen Absensi dengan Fitur Pengenalan Wajah dan GPS Menggunakan YOLO pada Platform Android - Hartiwi, Yessi; Rasywir, Errissya; Pratama, Yovi; Jusia, Pareza Alam (STMIK Budi Darma, 2020)
This study offers an attendance system that can be run with the Global Positioning System (GPS) feature to automatically check the location of the face owner. Recently, the YOLO algorithm is the world's most popular method of facial recognition. Currently the You Only Look Once (YOLO) algorithm toolbox has been provided in various programming language platforms for use. The system we offer is also able to check the position or whereabouts of objects using Global Positioning System (GPS) technology. The results of this test obtained an accuracy of 0.93435 and the lowest was within the range of 93%, while the average accuracy values were 93.26%. Of the 20 assessment data carried out by the Attendance Management System with Face Recognition and GPS Features using YOLO on the Android Platform. The evaluation of the accuracy of student attendance is expected to support the process of academic activities on campus. In addition, this product is expected to be able to assist management who require evaluation results as well as an effort to improve business processes in an agency in order to improve their performance. This research proves that the use of the tool library with the You Only Look Once (YOLO) algorithm is the most popular method in the world of facial recognition and is proven to be tough and very good at this time.